Penderitaan dan Respons Orang Percaya: Upaya Reflektif Kesetiaan bagi Spiritualitas Iman Kristen - Samuel Purdaryanto; Anton Santoso; Yonatan Alex Arifianto (STAK Reformed Remnant Internasional, 2023)
Suffering is something that is natural if avoided by humans, responding to suffering in the wrong way will produce negative things. This research aims to provide a correct understanding and concept of suffering as a reflective spirituality for the Christian faith. The writing of this article uses a qualitative approach and literature study. The results are as follows. First, believers can correctly understand the concept of suffering in Christian theology, so that believers have a positive attitude and response. Secondly, believers can understand the reflective concept in a philosophical and biblical perspective on suffering that is reflected for the faithfulness of believers as an awareness to accept the suffering that God allows. Through this, a person can have the right paradigm in dealing with suffering, then bring about loyalty and a person who relies on God when in suffering. In this study, the suffering experienced by Jesus and biblical figures provides an example that suffering is actually good for them.